Emerging Issues in Educational Technology - Yuni Noviana (Proceeding of the International Conference on Global Education and Learning, 2024)
The world of education is greatly influenced by advances in information and communication technology. (ICT). In recent decades, educational technology has developed rapidly, transforming various levels of education and learning methods. This article examines the latest educational technology issues, including innovations in software and learning platforms, ethical issues, the difficulties of implementing technology in schools, and how it can it has an impact on education policy. This study aims to identify problems, opportunities and consequences for future digital education using a more in-depth approach.